2008
DOI: 10.1002/ange.200604943
|View full text |Cite
|
Sign up to set email alerts
|

Lewis‐Base‐Katalyse in der organischen Synthese

Abstract: Das Erbe von Gilbert Newton Lewis (1875–1946) ist im Wörterbuch der chemischen Bindung und Reaktivität allgegenwärtig. Die Bedeutung seines Konzepts der Donor‐Akzeptor‐Bindung kommt in den eponymen Grundbegriffen für Elektronenpaarakzeptoren (Lewis‐Säuren) und ‐donoren (Lewis‐Basen) zum Ausdruck. Lewis erkannte, dass Säuren nicht automatisch Wasserstoff enthalten müssen (Brønsted‐Säuren) und trug so zum Sturz des “modernen Protonenkults” bei. Seine Entdeckung läutete zunächst die Entwicklung von Lewis‐Säuren a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
112
2
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 321 publications
(125 citation statements)
references
References 1,019 publications
(243 reference statements)
1
112
2
10
Order By: Relevance
“…The use of toluene and 0.55 equiv. of (i-PrCO) 2 O dramatically increased the s factor from 5.2 (Table 2, entry 12) to 12 ( Table 3, entry 1). Other low polarity solvents such as hexane, diethyl ether, and tert-amyl alcohol were not suitable because of the reduced solubility of the catalyst or higher freezing point.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…The use of toluene and 0.55 equiv. of (i-PrCO) 2 O dramatically increased the s factor from 5.2 (Table 2, entry 12) to 12 ( Table 3, entry 1). Other low polarity solvents such as hexane, diethyl ether, and tert-amyl alcohol were not suitable because of the reduced solubility of the catalyst or higher freezing point.…”
Section: Resultsmentioning
confidence: 95%
“…Other low polarity solvents such as hexane, diethyl ether, and tert-amyl alcohol were not suitable because of the reduced solubility of the catalyst or higher freezing point. It was found that the s factor increased when the temperature decreased (entries [1][2][3]. At À60 8C, the s factor for 1-phenylethanol reached 22 but the reaction rate was relatively slow and needed 64 h to give the desired product in a yield of 39% (entry 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[8] In the attempt to develop a catalytic methodology for the synthesis of functionalized cyclohexanecarboxylic acids, we have thought to take advantage of the recent progress in the field of organocatalysis, [9] where impressive results have been obtained in the activation of unsaturated ketones via amino catalysis. [10] Recently Melchiorre and List have reported that Cinchona-based primary amines can be exploited to activate a,b-unsaturated ketones and enals, [11] and reacted them via dienamine catalysis with different electrophilic partners, including nitroalkenes.…”
Section: Introductionmentioning
confidence: 99%